Pet Owners and Antibiotics: Knowledge, Opinions, Expectations, and Communication Preferences - Ri Scarborough (MDPI AG, 2021)
Despite the important role of antimicrobial use in companion animals in the global challenge presented by antimicrobial resistance (AMR), very few studies have quantified pet owner factors that can contribute to suboptimal veterinary antimicrobial use. We conducted an online survey of pet owners, asking about their experiences with veterinarians, their opinions on antibiotic use and knowledge of antibiotics, and their communication preferences regarding judicious prescribing. Just over half (54%) of the 558 pet owners had received antibiotics for their pet at their last non-routine veterinary consultation and most owners were happy (83%) with the antibiotic prescribing decision of their veterinarian. A quarter (25%) indicated that they had been surprised, disappointed or frustrated when a veterinarian had not given their pet antibiotics; 15% had explicitly requested them. Owners placed a higher priority on their pet receiving the most effective treatment than on treatment being cheap or convenient. Most respondents recognized the limitations of antibiotic therapy and the risks associated with antibiotic use, but 50% believed the risks were confined to the treated animal; only a minority was aware of inter-species transfer of bacteria. Pet owners indicated that they would find judicious prescribing messages focused on the direct risks of antibiotics to their pet more compelling than those about public health. Our findings suggest that veterinary communications about responsible antibiotic use should focus on pet owners’ priorities and address or bypass their gaps in understanding regarding antibiotic resistance.